Assessing The Role of Continuous Professional Development in Curriculum Adaptation Among Secondary School Teachers in Awka South Local Government Area - Nkolika, Chukwuka Judith (PT. Pusmedia Group Indonesia, 2024)
In today’s rapidly evolving educational system, the ability to adapt curricula to meet different student needs is more important than ever. Continuous Professional Development (CPD) has been suggested as a key factor in empowering teachers to enhance their curriculum adaptation skills. Hence, this study assessed the role of Continuous Professional Development (CPD) in enhancing curriculum adaptation among secondary school teachers in Awka South Local Government Area. Using a descriptive correlational research design, the study surveyed 117 teachers from both public and private schools, with a balanced representation of gender. Data was collected through a structured questionnaire, which was validated by three experts and tested for reliability using Cronbach’s Alpha (0.87). The data analysis method began with descriptive statistics, which included calculating the variables for gender, sample size (N), mean, standard deviation (Std. Deviation), and standard error of the mean (Std. Error Mean). The hypotheses testing method employed involved conducting an Independent Samples t-test, preceded by Levene's Test for Equality of Variances. The findings revealed that CPD significantly influences teachers’ ability to adapt the curriculum, providing them with innovative strategies, updated knowledge, and practical tools. The study highlighted that CPD plays an important role in addressing challenges faced by teachers, such as diverse student needs and curriculum changes. It concluded that CPD is essential for curriculum innovation and teacher professional growth. The study recommends continuous investment in CPD programs to enhance curriculum adaptation practices in secondary schools.